Climate Action in English for Computer Science - Dewi Sari Wahyuni; T. Sy. Eiva Fatdha (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study examines the integration of climate action concepts, specifically green computing and computing for green, into English language learning for computer science students using the Content and Language Integrated Learning (CLIL) approach. English Language Learners (ELLs), most of whom are non-native English speakers (NNES) in the field of Computer Science, require a language learning model that not only improves linguistic skills but also fosters awareness and active participation in global climate change issues. Through qualitative methods, including a literature review, CLIL classroom observations, and interviews with instructors, this study identifies best practices in designing content-integrated English language curricula that combine language proficiency and ecological literacy. Green computing principles are applied not only in learning materials but also in research methods to reduce carbon footprints. Findings indicate that integrating sustainability topics into English language learning within the context of Computer Science effectively enhances students' language skills and environmental awareness. Students become more motivated to act as agents of change in preserving the environment. The practical implication is that interdisciplinary collaboration and innovative CLIL curriculum design can play a crucial role in preparing Computer Science graduates to be not only technically competent but also linguistically competent, as well as having sustainability awareness.